Conductivity of YBCO ceramics in a wide range of temperatures and hafnium impurities concentrations - Savich, S.V.; Samoilov, A.V.; Samsonik, A.L.; Sukhov, V.N.; Tiutierieva, K.V.; Rusalovich, A.I.; Vovk, R.V.; Boynik, A.B.; Chroneos, A. (Functional Materials, 2016)
Conductivity of Hf doped YBa₂Cu₃O₇-δ ceramics was studied in the work. It was shown that introduction of Hf additive leads to increase of amount of scattering effective centers of the normal carriers. Excessive conductivity of the samples studied in a wide temperature range obeys the exponential temperature dependence, and near Tc satisfactorily described by the theoretical model of Aslamazov-Larkin. At the same time the Hf additive leads to significant increase of the temperature range of existence of the pseudogap anomaly in ab-plane.